On the temporal evolution of long‐wavelength mantle structure of the Earth since the early Paleozoic. (27th May 2015) - Zhong, Shijie; Rudolph, Maxwell L.
Abstract The seismic structure of the Earth's lower mantle is characterized by a dominantly degree‐2 pattern with the African and Pacific large low shear velocity provinces (i.e., LLSVP) that are separated by circum‐Pacific seismically fast anomalies. It is important to understand the origin of such a degree‐2 mantle structure and its temporal evolution. In this study, we investigated the effects of plate motion history and mantle viscosity on the temporal evolution of the lower mantle structure since the early Paleozoic by formulating 3‐D spherical shell models of thermochemical convection. For convection models with realistic mantle viscosity and no initial structure, it takes about ∼50 Myr to develop dominantly degree‐2 lower mantle structure using the published plate motion models for the last either 120 Ma or 250 Ma. However, it takes longer time to develop the mantle structure for more viscous mantle. While the circum‐Pangea subduction in plate motion history models promotes the formation of degree‐2 mantle structure, the published pre‐Pangea plate motions before 330 Ma produce relatively cold lower mantle in the African hemisphere and significant degree‐1 structure in the early Pangea (∼300 Ma) or later times, even if the lower mantle has an initially degree‐2 structure and a viscosity as high as 1023 Pas. This suggests that the African LLSVP may not be stationary since the early Paleozoic. With the published plate motion models and lower mantle viscosity of 1022 Pas, our mantle convection models suggest that the present‐day degree‐2 mantle structure may have largely been formed by ∼200 Ma.